Behaviour of Excess Stock Return Around Earnings Announcement Day: A Test of the Efficiency of the Kuala Lumpur Stock Exchange - Ahmadu Umaru Sanda; Ang Ji Li; G. S. Gupta (Asian Academy of Management Journal, 1998)
Behaviour of Excess Stock Return Around Earnings Announcement Day: A Test of the Efficiency of the Kuala Lumpur Stock Exchange (PDF not available)